HISTORY OF FORMATION AND ANALYTICAL REVIEW OF COLLECTION FUNDS OF THE MAIN BOTANICAL GARDEN (ALMATY) (Experimental biology, 2024)
An overview of the dynamics of the quantitative composition of the Main Botanical Garden’s (MBG)  living collections from the time it was formed to the present day is given. The distribution of taxa by expositions and collection sites, their systematic affiliation, peculiarities of the formation of collections in different periods of the existence of MBG, and features of ontogeny in different groups of taxons are discussed.The combined living collection fund of the MBG includes 3225 taxa of higher plants in 150 families, 667 genera, 1853 species, 343 forms, and 1076 plant varieties representing domestic and worldwide flora from different regions of the globe. The most represented families are Asteraceae, Lamiaceae, Rosaceae, and Fabaceae however, most families (78) are represented by only 1-2 species.
Keywords: Kew words: living collections, exposition, taxa, plant species, ontogenesis